[PP.23.17] PREDICTORS OF LONG TERM SUCCESS IN RENAL DENERVATION. (September 2016) - Fischer, G.; Eckert, S.
Abstract : Objective: We studied the importance of the duration of treatment and norepinephrine levels with respect to long term success of renal denervation. Figure. No caption available. Design and method: In this prospective cohort study with 54 patients suffering from resistent hypertension, 22 women and 32 men, 62 years old SEM ± 1.4, first diagnosed 13.8 years ago SEM ± 1.7, receiving 5.3 SEM ± 0.2 hypertension lowering agents, norepinephrine levels were measured at standardardised conditions before intervention and after 6 and 12 months. Two devices were used: Medtronic SimplicityTM (n = 45) and St. Jude Medical EnligHTNTM (n = 9) Patients hypertension was treated about 14 years with different combinations of medical therapy. Data analysis were performed with Graphpad Prism Software using the Student's t-test. A p-value < 0.05 indicates a statistically significant difference. Results: Please see images in the previous page. Conclusions: Norepinephrine levels, but not the duration of hypertension, could be a predictor for long time success in renal denervation.